Radiation Detector Circuit - Tee, Kian Siang (Universiti Sains Malaysia, 2017)
This thesis is focused on building a radiation detector circuit along with the Arduino Uno microcontroller. Nowadays, radiation is commonly being used in several fields such as medical field and communication field. However, radiation is still harmful to all of us if it is in a large dose. Therefore, a radiation detector circuit is built in order to detect the existence of radiation. In this project, AM-241 is used as the radiation source. AM-241 emits mainly alpha radiation and the SiC photodiode is used as the radiation sensor. To deal with this project, a transimpedance amplifier circuit is built as the interface between Arduino Uno microcontroller and the SiC photodiode. Then, the output voltage is fed into any analog pin of the Arduino Uno microcontroller. The Arduino Uno microcontroller is programmed to calculate the values like the output voltage and the current passing through the SiC photodiode. All these values are displayed on the LCD and also compared to the values measured by using the multimeter. The difference between both has been analyzed and there is almost no difference. The performances of the SiC photodiode and the transimpedance amplifier circuit have also been analyzed. The possible reasons of why Am-241 alpha radiation is undetectable by the SiC photodiode have been revealed. Yet, the main reason is that of the weak strength of the Am-241 alpha radiation.